High-performance liquid chromatography with fluorescence detection for the determination of nitrofuran metabolites in pork muscle - Liang-Quan Sheng; Ming-Ming Chen; Shui-Sheng Chen; Na-Na Du; Zhao-Di Liu; Chong-Fu Song; Rui Qiao (Food Additives & Contaminants: Part A, 2013)

Potato leafroll virus (PLRV) and Potato virus Y (PVY) influence vegetative growth, physiological metabolism, and microtuber production of in vitro-grown shoots of potato (Solanum tuberosum L.) - Jing-Wei Li; Biao Wang; Xiao-Ming Song; Ren-Rui Wang; Long Chen; Hao Zhang; Zhi-Bo Zhang; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

In vitro mutagenesis and directed screening for salt-tolerant mutants in peanut - Ming-Xia Zhao; Hai-Yan Sun; Rui-Rui Ji; Xiao-Hui Hu; Jiong-Ming Sui; Li-Xian Qiao; Jing Chen; Jing-Shan Wang (Euphytica, 2013)

Priming of Anti-Herbivore Defense in Tomato by Arbuscular Mycorrhizal Fungus and Involvement of the Jasmonate Pathway - Yuan Yuan Song; Mao Ye; Chuan You Li; Rui Long Wang; Xiao Chen Wei; Shi Ming Luo; Ren Sen Zeng (Journal of Chemical Ecology, 2013)

Treatment with exogenous hydrogen sulfide attenuates hyperoxia-induced acute lung injury in mice - Huai-Dong Li; Zhao-Rui Zhang; Qing-Xiang Zhang; Zhi-Chu Qin; Deng-Ming He; Jin-Song Chen (European Journal of Applied Physiology, 2013)

Identification of 40k γ-secalin genes - PENG-FEI QI; QING CHEN; THÉRÈSE OUELLET; CHENG-XING LE; JIA AI; YU-MING WEI; JI-RUI WANG; YOU-LIANG ZHENG (Journal of Genetics, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .